Poetry Slam: a bofetada como instauração da pedagogia pública - Carvalho, Marina Maria Pereira de (2022)
The present academic work establishes an articulation between poetry slam that has been taking place in Brazil and Public Pedagogy. To this end, as methodology, focus group was chosen and it was carried out with five female poets who participate in poetry slam battles in order to, from the poets' perspectives, generate hypotheses about the relationship of poetry slam and politics, aesthetics, processes of subjectivation and Public Pedagogy. Using a theoretical critical approach, mainly from the work of Jacques Rancière, Gilles Deleuze and Félix Guattari, this study was divided into five sections. In the first section, a brief presentation of the entirety of the work and its structure was presented, showing the route of the cartographic clues that helped us in the building of this research. In the second section, the methodological and affective choices that guided the work were detailed, indicating how the encounter with the poetry slam, the online and in-person events and the poets who participated in the focus group took place. Also in the second section, the poetry slam, its rules, its main themes and how it has been gaining ground on the streets of Brazil and the world is detailed. In a purposeful way, the concept of “bofetada” (“slap”) was created as a reading key that will serve to make the slam visible as the establishment of the public sphere. In the third section, the concepts of Jacques Rancière, Gilles Deleuze and Félix Guattari guide the reflections on politics, aesthetics and processes of subjectivation which will be discussed and articulated to the poetry slam as “bofetada” in this study. In the fourth section, Social Pedagogy, Social Education and Non-Formal Education will be discussed as educational perspectives that are aware of the production of social inequality and elaborate forms of confrontation and resistance, mainly outside school walls. Then, still in the same section, the conceptual formulations of Public Pedagogy developed by both Henry Giroux and Gert Biesta will be presented. However, the formulation of the latter author will be taken as a reference to think of Public Pedagogy as settling of the public sphere. Finally, in the fifth section, this study will discuss neoliberalism as a rationality that invests in the hypervaluation of the self, in individual freedom, in competitiveness, manufacturing individualities and disarticulating the public sphere. Based on the Judith Butler approach, this work will show how bodies in assembly make their appearance in the public sphere, resisting neoliberal processes of existence as well as founding the public sphere itself. Also, this study will present how in the face of police states, policies of silencing, exclusion and eliciting sadness, poetry slam as “bofetada” engender dissent capable of confronting the current order and of producing a Public Pedagogy.